Liraglutide reduces the body weight and waist circumference in Chinese overweight and obese type 2 diabetic patients - FENG Ping; YU De-min; CHEN Li-ming; CHANG Bao-cheng; JI Qiu-di; LI Shu-ying; ZHU Mei; DING Sheng-hua; ZHANG Baozhen; WANG Su-li; LI Hong-tao; LIN Jing-na; et al. (Acta Pharmacologica Sinica; Vol 36, No 2 (February 2015): Acta Pharmacologica Sinica, 2017)
Aim: To investigate the effects of liraglutide, a glucagon-like peptide-1 (GLP-1) receptor activator, on body weight and waist circumference in Chinese overweight and obese type 2 diabetic patients. Methods: A total of 328 Chinese overweight and obese type 2 diabetic patients were included in this multi-center, open-labeled and self-controlled clinical study. The patients were subcutaneously injected with liraglutide once daily for 24 weeks as add-on therapy to their previous hypoglycemic treatments. Statistical analyses were performed using SPSS software package version 11.5 for Windows. Results: Liraglutide treatment caused significant reduction of the mean body weight (from 86.61±14.09 to 79.10±13.55 kg) and waist circumference (from 101.81±13.96 to 94.29±14.17 cm), resulting in body weight lose of 5%–10% in 43.67% patients, and body weight loss above 10% in 34.06% patients, who had significant lower plasma creatinine levels. Baseline waist circumference, BMI and HOMA-IR were independently correlated with the body weight loss. Furthermore, liraglutide treatment significantly decreased HbA1c levels (from 8.66%±2.17% to 6.92%±0.95%) with HbA1c